Pengaruh Terapi Pemaafan La-Tahzan dalam Meningkatkan Penerimaan Diri Istri yang Mengalami Kekerasan dalam Rumah Tangga - Andhita Dyorita Khoiryasdien; Koentjoro Soeparno (JIP (Jurnal Intervensi Psikologi), 2015)
Husband's infidelity is one of the existence of the cause of domestic violence resulting in low self-acceptance wife. LaTahzan forgiveness therapy aims to help the wife as the victim of violence to be able to break loose from negative feelings, improving both themselves and condition became more positive, and find a new purpose in life to get closer to Allah SWT as a God. Subjects in this study amounted to three wives who are victims of violence and infidelity. Data was collected through action research approach and use the scale self-acceptance, observation and interviews. Measurement of self-acceptance scale is performed three times that are before the intervention, after an intervention, and follow up by two weeks post intervention. The data used quantitative and qualitative. Quantitative analysis is used, based on measurements on a scale of self-acceptance. Qualitative analysis was conducted based on the outcome document of observations and interviews during the assessment phase to the follow-up phase. The results showed that the La-Tahzan Forgiveness therapy can provide a change towards a better subject in an effort to increase self-acceptance wife who experienced domestic violence.Keywords: La-Tahzan Forgiveness Therapy, domestic violence, Self-Acceptance,Infidelity